Annotated catalogue of the carabid beetles of the Republic of Macedonia (Coleoptera: Carabidae) - Hristovski, Slavčo; Guéorguiev, Borislav (Zootaxa, 2015)
The catalogue of the ground beetles (Coleoptera: Carabidae) of the Republic of Macedonia is the result of our permanent investigation during 15 years. It is based on the critical review of the data in 255 scientific publications and the revision of the collections deposited in the museums in Macedonia (Skopje and Struga), other European countries (Berlin, Budapest, Vienna, Sofia) and the first author’s private collection. For all of the species and subspecies we have presented the known literature references, precise data for the studied material and overall distribution in the Republic of Macedonia. The study of the material resulted in new country records of 10 genera, 101 species and 25 subspecies. First detailed records are provided for another 47 species and subspecies, and additional material was studied of 482 species and subspecies. Type material of 18 species and subspecies was also examined. Thirteen species and one subspecies were rejected from the list of Macedonian ground beetles. Six more species are treated as questionable and were not included in the present list. As a result, the presence of 571 species and 234 subspecies (626 taxa in total) in Macedonia is confirmed. These taxa are arranged in 104 genera, 31 subtribes, 35 tribes and 13 subfamilies. The most numerous in term of the species are the genera Bembidion (60), Harpalus (48) and Amara (46), as well as Pterostichus (26), Ophonus (19), Carabus (16), Trechus (16), Brachinus (16) and Dyschirius (15).